2020
DOI: 10.1016/j.physio.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

First point of contact physiotherapy; a qualitative study

Abstract: Objectives First point of contact physiotherapy (FPCP) provides patients direct access to a physiotherapist. Literature demonstrates efficacy of FPCP. Evidence has highlighted the need for cultural shifts from both patient and professional perspectives to optimise FPCP. This study explored stakeholder perceptions of patient awareness and understanding of FPCP to better inform FPCP implementation. Design, setting, participants A qualitative methodology utilised semi-structured interviews and focus groups. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 27 publications
8
40
0
2
Order By: Relevance
“…This study highlighted the importance of receptionists in signposting patients to the FCP role, and the frequent expectation that the GP was the first step for assessment, a finding present in wider evidence (Goodwin et al, 2020). However, receptionists are faced with time challenges, preventing them consistently explaining new consultation methods to patients (Brant et al, 2018).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This study highlighted the importance of receptionists in signposting patients to the FCP role, and the frequent expectation that the GP was the first step for assessment, a finding present in wider evidence (Goodwin et al, 2020). However, receptionists are faced with time challenges, preventing them consistently explaining new consultation methods to patients (Brant et al, 2018).…”
Section: Discussionmentioning
confidence: 63%
“…However, receptionists are faced with time challenges, preventing them consistently explaining new consultation methods to patients (Brant et al, 2018). Goodwin et al (2020) found that the receptionist role was effective, but only if they understood the aims of the FCP service. Practice B was in a network of Practices that could access the FCP role, and there were inconsistencies in receptionists' explanations of the FCP role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multimedia platform enabled the profession to be portrayed in a new inspirational light to audiences, demonstrating the impact that imagery can have when used to shape new narratives. Research has revealed that public awareness of physiotherapy in the UK is poor, and those authors called for new methods of informing the public about the profession [ 32 ]. And in 2018, Zadro [ 33 ] argued that we need to promote physiotherapy using information based on research findings.…”
Section: Kt Innovationmentioning
confidence: 99%
“…Goodwin et al (2020), em um estudo quantitativo sobre o fisioterapeuta como profissional de primeiro contato, relata que as técnicas tradicionais de marketing (pôsteres, panfletos e manequins de tamanho real) que eram utilizadas para disseminar a abordagem, mostraram-se em maior parte dos casos ineficazes. Os autores apontam que o marketing baseado em evidências é muito importante para a fisioterapia e que novas técnicas devem ser difundidas na profissão.…”
unclassified